2012
DOI: 10.5606/tjr.2012.005
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Some Combined Conservative Methods in the Treatment of Carpal Tunnel Syndrome: A Randomized Controlled Clinical and Electrophysiological Trial

Abstract: Bu çalışmada, hafif karpal tünel sendromu (KTS) tedavisinde bazı konservatif yöntemlerle birlikte uygulanan deksametazon iyontoforezi veya ultrason veya plasebo iyontoforezin (deksametazonsuz) etkinliği karşılaştırıldı. Hastalar ve yöntemler: Elektromiyografi ile doğrulanmış hafif KTS tanılı 58 hasta çalışmaya dahil edildi. Hastalar rastgele üç gruba ayrıldı: (i) deksametazon iyontoforezi ile tedavi edilen iyontoforez grubu (n=20); (ii) ultrason ile tedavi edilen grup (n=20) ve (iii) plasebo iyontoforezi uygul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(25 citation statements)
references
References 29 publications
1
22
0
Order By: Relevance
“…For the treatment of CTS, Atroshi and Gummesson claimed that patients could be successfully managed without surgery 2 ) . Standard conservative treatment may effectively relieve symptoms and improve functional status 22 ) , and may also reduce the number of patients who need surgery, especially during the early stages of management 23 ) . Elfar et al stated that conservative therapy generally offers only temporary relief of symptoms 7 ) .…”
Section: Discussionmentioning
confidence: 99%
“…For the treatment of CTS, Atroshi and Gummesson claimed that patients could be successfully managed without surgery 2 ) . Standard conservative treatment may effectively relieve symptoms and improve functional status 22 ) , and may also reduce the number of patients who need surgery, especially during the early stages of management 23 ) . Elfar et al stated that conservative therapy generally offers only temporary relief of symptoms 7 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several studies reported optimum results with the use of neurodynamic mobilization as a conservative treatment, with neural slipping helping nerve mobilization in relation to musculoskeletal tissues. 2,17 The biomechanical effect of the treatment would restore neural mobilization by decreasing the edema and adhesion in the carpal tunnel. 7,18,19 Because of the chronicity of CTS, studies also described neuromodulator effects from neural mobilization techniques such as the decrease in nociception of the median nerve; reduction in algogenic and pro-inflammatory substances 20 ; and reversibility in the pain pathways previously modified.…”
Section: Introductionmentioning
confidence: 99%
“…17 However, some studies have demonstrated the efficacy of ultrasound therapy on NCV in mild-to-moderate CTS. 18,19 Additionally, corticosteroid phonophoresis, steroids, and procaine hydrochloride injection treatments in patients with CTS have improved electrophysiological parameters. 20,21 Improved electrophysiological parameters with pulsed SWD treatment reported herein suggest that this treatment might also have thermal effects.…”
Section: Discussionmentioning
confidence: 99%